2016
DOI: 10.1007/s40264-016-0414-0
|View full text |Cite
|
Sign up to set email alerts
|

Linking MedDRA®-Coded Clinical Phenotypes to Biological Mechanisms by the Ontology of Adverse Events: A Pilot Study on Tyrosine Kinase Inhibitors

Abstract: Introduction A translational bioinformatics challenge lies in connecting population and individual’s clinical phenotypes in various formats to biological mechanisms. The Medical Dictionary for Regulatory Activities (MedDRA®) is the default dictionary for Adverse Event (AE) reporting in the FDA Adverse Event Reporting System (FAERS). The Ontology of Adverse Events (OAE) represents AEs as pathological processes occurring after drug exposures. Objectives The aim is to establish a semantic framework to link biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
(38 reference statements)
0
15
0
Order By: Relevance
“…The OAE is a community-driven ontology developed to standardize and integrate data relating to AEs arising subsequently to medical interventions (e.g., medication and vaccination), as well as to support computer-assisted reasoning ( He et al, 2014 ). Previous studies have shown that OAE performed well in the analysis of AE data associated with vaccines and drugs ( Sarntivijai et al, 2012 , 2016 ; Xie et al, 2016a , b ). In this study, the OAE was used for representing and classifying the AEs associated with the three brucellosis vaccines in animals and humans.…”
Section: Methodsmentioning
confidence: 96%
“…The OAE is a community-driven ontology developed to standardize and integrate data relating to AEs arising subsequently to medical interventions (e.g., medication and vaccination), as well as to support computer-assisted reasoning ( He et al, 2014 ). Previous studies have shown that OAE performed well in the analysis of AE data associated with vaccines and drugs ( Sarntivijai et al, 2012 , 2016 ; Xie et al, 2016a , b ). In this study, the OAE was used for representing and classifying the AEs associated with the three brucellosis vaccines in animals and humans.…”
Section: Methodsmentioning
confidence: 96%
“…The OAE general framework has been applied to represent and study AEs associated with vaccines in the Ontology of Vaccine Adverse Events (OVAE) [28], neuropathy-inducing drugs in ODNAE [29], and drugs used to treat cardiovascular diseases in OCVDAE [27]. OAE also provides a way to link different domains of entities such as medical administration, anatomic entities, phenotypes, and patient qualities, and cross-reference other controlled terminologies such as the Common Terminology Criteria for Adverse Events (CTCAE) [49] and the Medical Dictionary for Regulatory Activities (MedDRA) [50]. It has become clear that biological ontologies support the integration of biological knowledge for learning and predicting ADEs [51].…”
Section: Discussionmentioning
confidence: 99%
“…28 The cardiovascular adverse events associated with 5 TKIs/mAbs, namely, dasatinib, imatinib, lapatinib, cetuximab, and trastuzumab, were extracted from reports in FAERS. This analysis produced 1053 cardiovascular MedDRA terms, of which 884 were unique terms that were not in OAE.…”
Section: Development Of Oae To Capture Adverse Event In An Ontologicamentioning
confidence: 99%